Sensitization of human malignant lymphoid cells to etoposide by fucoidan, a brown seaweed polysaccharide - Philchenkov, A.; Zavelevich, M.; Imbs, T.; Zvyagintseva, T.; Zaporozhets, T. (Experimental Oncology, 2007)
The search for the substances sensitizing cancer cells to apoptosis induction by chemotherapeutic agents is a task of high importance in the modern strategy of anticancer therapy. The aim of the study was to investigate the apoptogenic and apoptosis-modulating activities of fucoidan (sulfated polysaccharide) isolated from far-eastern brown seaweeds Fucus evanescens in two human malignant lymphoid cell lines, MT-4 and Namalwa. Methods: Apoptosis was assessed morphologically and quantified by flow cytometry analysis of cells stained with propidium iodide. Caspase-3 activation was assayed by flow cytometry with the aid of labeled monoclonal antibodies. Results: The fucoidan at 500 µg/ml was not cytotoxic in MT-4 or Namalwa cells even in the setting of long-term presence in culture medium up to 14 days. Nevertheless, pretreatment of MT-4 but not Namalwa cells with fucoidan followed by the exposure to DNA topoisomerase II inhibitor etoposide led to about two-fold increase in the relative apoptotic index as compared with etoposide alone. Apoptosis enhancement of MT-4 cells by fucoidan was not accompanied by further increase in the number of the cells with active form of caspase-3. Conclusion: The present findings demonstrate for the first time that fucoidan enhances etoposide induced caspase-dependent cell death pathway in MT-4 but not Namalwa cell line. The mechanisms of such enhancement do not seem to be related directly to caspase-3 activation.